Cover Image, Volume 87, Issue 2. Issue 2 (19th January 2019) - Gay, Jamie C.; Eckenroth, Brian E.; Evans, Chiara M.; Langini, Cassiano; Carlson, Samuel; Lloyd, Jonathan T.; Caflisch, Amedeo; Glass, Karen C.
Abstract : Reverse Cover: The cover image is based on the Structure Note Disulfide bridge formation influences ligand recognition by the ATAD2 bromodomain by Jamie C. Gay et al., DOI:10.1002/prot.25636 .